Ordinances of Jersey City 41 (1874) - (:unkn) unknown (My University, 1874)
In Relation to the Sidewalks, Public Grounds and Streets in Jersey City: No person shall, within this city, fire or discharge any gun, pistol, cannon, or fowling piece or other fire-arms, unless in defense of his property or person
Keywords: DISCHARGE